Perspective on the Development and Validation of Ab Reagents to Fish Immune Proteins for the Correct Assessment of Immune Function - Dixon, Brian; Barreda, Daniel R.; Sunyer, J. Oriol (Frontiers in Immunology, 2018)
Understanding of immune function in humans and model organisms, such as mice, has advanced in the last few decades because of technological advances and availability of reagents. While genomic technologies have helped to increase knowledge, many advances in immunology have occurred because of tools for identifying and sorting different cell types and subtypes (antibodies for cell surface markers), cell culture and imaging technology (antibodies for immunohistochemistry) and identifying the protein products of cells (quantitative ELISA and ELISpot assays). It is important for scientists to realize the advantages and disadvantages of each technique, in particular the limits of what each technology can tell you about immune function. In light of this, we would like to offer some insight and discussion points based on our research experience in that area.